Neviditelná skupina aneb Co s postdoktorandy? / The invisible group, or what to do with postdocs? - Jiří Mareš (Pedagogická Orientace, 2013)
The paper aims 1. to draw attention to the situation in the Czech Republic, where universities „produce“ tens of PhD graduates every year and are little interested in their future; 2. to clarify the term „postdoc“ and introduce research studies that deal with this group of university graduates; 3. to present some information about PhD graduates in the field of educational sciences in the Czech Republic; 4. to discuss the Czech context that influences the employment of postdocs; 5. to summarize findings from abroad about systematic work with postdocs. In the first part we describe the current situation in the Czech Republic and abroad. In the second part we introduce the research study about the number of successful graduates from educational sciences doctoral programmes. The third part focuses on the Czech context that influences the employment of postdocs. The fourth part summarizes the experience from other countries considering systematic work with postdocs. In our research study we found that 549 people successfully completed a doctoral programme in educational sciences in 1999–2011. Systematic work with postdocs has been initiated at three universities(Charles University, Masaryk University, Palackého University) but is at its outset. From the above mentioned it follows that in the Czech context it will be necessary to monitor where postdocs work, to what degree they focus on research, and what their career path looks like. Besides this, it will be crucial (based on experience from abroad) to devise a system that will allow postdocs to follow various paths when it comes to broadening their knowledge and improving their skills.